Development and evolution of segmentation assessed by geometric morphometrics: The centipede Strigamia maritima as a case study. Issue 3 (May 2017) - Savriama, Yoland; Gerber, Sylvain; Baiocco, Matteo; Debat, Vincent; Fusco, Giuseppe
Abstract: Using the centipede model species Strigamia maritima as a subject of study, we illustrate the potential of geometric morphometrics for investigating the development and evolution of segmentation, with a specific focus on post-embryonic segmental patterning. We show how these techniques can contribute detailed descriptive data for comparative purposes, but also precious information on some features of the developmental system that are considered relevant for the evolvability of a segmented body architecture, such as developmental stability and canalization. Morphometric analyses allow to separately investigate several sources of phenotypic variation along a segmented body axis, like constitutive and random segment heteronomy, both within and among individuals. Specifically, in S. maritima, the segmental pattern of ventral sclerite shapes mirrors that of their bilateral fluctuating asymmetry and among-individual variation in associating the most anterior and most posterior segments in diverging from the central ones. Also, among segments, there seems to be a correlation between fluctuating asymmetry and shape variation among individuals, suggesting that canalization and developmental stability are somehow associated. Overall, these associations might stem from a joint influence of the segmental position on the two processes of developmental buffering. Graphical abstract: Highlights: Morphometrics is an ideal tool for studying the evolution of segmentation. Morphometric analyses allow to tease apart several sources of phenotypic variation. In a centipede, canalization and developmental stability are possibly associated.